Efficacy and Tolerability of a Hepatoprotective Nutraceutical Formulation in Dogs with Iatrogenic Hepatocellular Injury: A Retrospective Observational Study - Felice, Bruna; Barbato, Gianluca; Paoli, Elisa; D’Orta, Barbara; Khalidy, Youssef; Pascali, Francesco; Pantalone, Barbara; Rosi, Paolo; Trussardi, Greta; Zucca, Alessandra; et al. (British Journal of Healthcare and Medical Research, 2026)
Objective: To evaluate longitudinal changes in hepatocellular enzyme activity in dogs nutritionally supplemented with a complementary feed 1 based on carrot ( Daucus carota L. ) extract rich in superoxide dismutase (SOD) from phytocomplexes, to modulate hypertransaminasemia induced by therapies for canine leishmaniasis. Methods: Retrospective observational study of 30 client-owned dogs with alanine aminotransferase (ALT) and aspartate transaminase (AST) activity 4 times the reference limit at T0 and reevaluated every month. The endpoints: ALT, AST were assessed at T0, T3, T6, and T12 months. Statistical analysis: ANOVA for repeated measures with Bonferroni correction and Effect Size ( Cohen’s D ). Results: ALT activity decreased significantly at T12 - P < .001 . Ninety percent of dogs achieved biochemical normalization within 12 months. Tolerability was 96%. Conclusions: Supplementation showed a clinically relevant reduction in cytolysis markers . The robustness of the effect ( Cohen’s d = 2.8 ) supports the efficacy of the formulation in the support of iatrogenic liver injury. Observation and Limitations: Retrospective design • No untreated control group • Limited biomarker panel • No histopathological confirmation • Moderate sample size. Retrospective analysis of medical records; no experimental interventions were performed.